99 years of Italian-Czech, Czech-Italian bilingual lexicography - Palmarini, Luca (Romanica Olomucensia, 2024)
The article aims to analyse the first 99 years of Italian-Czech, Czech-Italian bilingual lexicography, from its origins, dated 1890, up to 1989, the year of the fall of Communism in Czechoslovakia. After having briefly introduced the literary and linguistic relationships of Bohemia and Moravia with the Italian peninsula, the paper focuses on the lexicographic ones, starting with some references to the multilingual dictionaries in which Czech and Italian are present, then moving on to the path of history of Italian-Czech, Czech-Italian bilingual dictionaries and its lexicographic analysis. The analysis is in a diachronic key; the methodology adopted is of a comparative nature, with references to lexicultural elements, also in relation to other coeval bilingual dictionaries. The results obtained have allowed the reconstruction of the history of the first 99 years of the bilingual lexicography in question, the identification of two phases (1890-1940; 1945-1989), and the highlighting of the purposes of the individual works and some of their lexicographic characteristics and contents that allow us to characterise them in "dictionaries" and "small dictionaries". The research shows that the initial path of Italian-Czech, Czech-Italian bilingual lexicography is significantly influenced by the German model that was dominant at date. Several factors (the minor role of the Czech language, the lack of an independent state until 1918, and the end of the communist regime) have resulted in the prevalence of works of meagre content; only a few are real dictionaries. However, the unidirectional works confirm the continuous interest of the Czech community in the Italian language.
Keywords: bilingual lexicography; Czech-Italian dictionaries; history of lexicography; history of Italian language